Comparison of species diversity and abundance of ants in grassland and reforestation area at Lai Nan sub district, Wiang Sa district, Nan province - Wissanee Suppasan (Chulalongkorn University, 2013)
Thesis (M.Sc.)--Chulalongkorn University, 2011